شخصيات مميزة في روايات د۔ نجيب الكيلاني: Distinguished Characters in Dr. Najeeb Al-Kilani’s Novels - خنساء الجاجي (الدراسات الإسلامية, 2024)
Najeeb al-Kilani’s novels are distinguished for their rich tapestry of characters, each constructed with a distinctive essence that reflects the author’s deliberate narrative choices and thematic objectives. These characters are not mere figures within his stories; they are vibrant entities that capture the imagination through their unique attributes and multifaceted personalities. What unites them is a shared quality of distinction, making them unforgettable within the literary realm. This research aims to explore a selection of such characters, focusing on their unique characteristics and the reasons they merit academic analysis. The study probes into al-Kilani’s ability to infuse his characters with traits that evoke fascination and critical thought. These characters often stem from various sources, such as a profound human connection, a sense of strangeness, sharp wit, extraordinary acts of heroism, or intense suffering. Additionally, some characters stand out due to their impactful roles in the narrative, portrayal of unique life experiences, or embodiment of human contradictions. These elements make the characters distinctive and reflect broader human conditions and social issues, adding depth and resonance to al-Kilani’s works By examining these aspects, the research seeks to understand how al-Kilani’s characters transcend the boundaries of conventional storytelling to become symbols of human complexity. Each character chosen for this study represents a particular facet of al-Kilani’s literary genius, whether through their profound emotional depth, ability to surprise and inspire, or capacity to challenge readers’ perceptions. This study also highlights the writer’s narrative strategies, exploring how his characters’ distinctiveness aligns with his broader artistic and philosophical goals. This research underscores the enduring relevance of Najeeb al-Kilani’s contributions to Arabic literature by thoroughly examining these characters. It aims to provide new insights into his approach to character development and inspire further scholarly engagement with his works. This study celebrates the artistry and intellectual depth that define his literary legacy by focusing on the human, the extraordinary, and the paradoxical within al-Kilani’s novels.